Criminal Subculture Of Street Teenagers - Azis, Ratna (Opción, 2019)
This study is intended to explore the experience of the criminal subculture in Indonesia. This research was conducted in the City of Heroes (a pseudonym), in particular, in East Java, Indonesia. This study used qualitative methods to assess the informants who are acting against the law. This study found that the teenagers conflicting with the law generally have similar social backgrounds and conditions as they come from poor and mostly broken-home families. The desire to be accepted by the group requires them to adjust and obey the values held by the subculture group, which also becomes the identity of the teenagers who are in conflict with the law. Besides their ongoing adaptation to the values of the group, they also have to survive in the middle of alcoholism and drugs. This is often done by selling alcohol and drugs to other street children.